Positioning Laser Line Detection Algorithm of Construction Robot Based on LSD and Improved Least Squares Method - Xu, Chunyu; Dou, Jianping; Feng, Zhuotao (2023 29th International Conference on Mechatronics and Machine Vision in Practice (M2VIP), 2023)
A laser line detection algorithm for the positioning of construction robots based on Line Segment Detector (LSD) and an improved least squares method (LSM) is proposed to address the line finding and localization requirements in actual construction operations. After preprocessing and edge detection of the input image, the LSD algorithm is utilized to detect line segments representing the laser lines for positioning. These line segments are then converted into a point set containing information about the laser lines' positions. To overcome the limitations of traditional least squares method that relies on vertical errors, an improved least squares method is employed to fit the centerline of the laser lines, which serves as a reference for subsequent robot localization. Experimental results demonstrate that the proposed algorithm accurately detects and fits the centerline of the laser lines in the input image, and exhibits high robustness and accuracy.